Лошади ранних кочевников - Секерская, Е.П. (Материалы по археологии Северного Причерноморья, 2011)
In the article is discussed origin and pedigree belonging of horses from Early Scythian burials of Eurasian steppes. Measures bones and their indexes are produced in order to determine height of animals in withers, massiveness of bones, main pace of horse and landscape-climatic conditions forming of breeds.